2000
DOI: 10.1136/bjsm.34.2.125
|View full text |Cite
|
Sign up to set email alerts
|

The pathological status of exercise dependence

Abstract: In the absence of an eating disorder, women identified as being exercise dependent do not exhibit the sorts of personality characteristics and levels of psychological distress that warrant the construction of primary exercise dependence as a widespread pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
97
2
8

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(114 citation statements)
references
References 37 publications
7
97
2
8
Order By: Relevance
“…The importance of compulsive attitudes has also been highlighted in research related to a conceptual model of understanding the relationship between EEDs 36. Addiction models of excessive exercise report that withdrawal symptoms related to negative affect such as guilt, anxiety, and depression are involved in maintenance 37. In the EED, consequences of not exercising are included that are related to eating disorder symptoms, such as difficulty with regular meals and changes in perceived body image when they do not exercise.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of compulsive attitudes has also been highlighted in research related to a conceptual model of understanding the relationship between EEDs 36. Addiction models of excessive exercise report that withdrawal symptoms related to negative affect such as guilt, anxiety, and depression are involved in maintenance 37. In the EED, consequences of not exercising are included that are related to eating disorder symptoms, such as difficulty with regular meals and changes in perceived body image when they do not exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Kern (2010) found that exercise addiction was positively related to Neuroticism and Openness among students, whereas it was positively related to Agreeableness and Openness among recreational practitioners. Another study found that exercise dependent individuals scored higher on Neuroticism than a control group (Bamber, Cockerill & Carroll, 2000). Hausenblas and Giacobbi (2004) found exercise addiction to be positively related to Extroversion and Neuroticism and negatively related to Agreeableness.…”
Section: Introductionmentioning
confidence: 99%
“…The Exercise Attitudes and Beliefs Questionnaire (EABQ) was administered to control for the possible co-morbidity of exercise dependence and disordered eating (Davis et al, 1995(Davis et al, , 1997Epling and Pierce, 1988;Bamber et al, 2000). The EABQ is a 12-item questionnaire generated from the diagnostic criteria of exercise dependence in women proposed by Bamber and her colleagues on the basis of a qualitative study of exercise attitudes and behaviour in 56 female exercisers (Bamber et al, 2003).…”
Section: Control and Confounding Variables 231 Exercise Dependencementioning
confidence: 99%